The Digital Rupiah and The Future of Accountants: A Central Bank Digital Currency (CBDC) Study - Zahrani, Syifa Aulia; Sendjaja, Theodorus (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2025)
The financial sector has undergone digital transformation, including establishing digital currency issued by central banks (CBDC) such as Digital Rupiah, which has transformed Indonesia's payment and monetary systems. These changes are expected to have a major impact on the roles and competencies of accountants, who are responsible for ensuring financial transparency, accountability and efficiency. This research examines the effects of Digital Rupiah on accountants' work, such as changes in financial reporting, auditing, and risk management. This research utilises a qualitative methodology, which includes a literature study to gauge accountants' readiness for the Digital Rupiah. The results show that Digital Rupiah can improve the efficiency of financial transactions and open up new opportunities for the accounting profession, such as requiring expertise in blockchain technology and digital financial data analysis. But issues such as unfamiliarity with technology and unwillingness to change must be overcome. This research finds that Digital Rupiah is not only a monetary innovation but also transforms the accounting profession. These results add to the literature on digital accounting developments and help professional accountants anticipate the future of CBDC-based financial systems.